The effectiveness of waste management education on students' knowledge and behavior at the Ministry of Health Polytechnic of Padang - Riyana Husna; Vebby Amellia Edwin; Sri Wahyuningsih; Mahaza Mahaza; Darwel Darwel; Lindawati Lindawati; Welly Welly (Indonesian Journal of Health Science, 2026)
Waste management is an environmental issue that requires active community participation, including students as agents of change. One effective approach is the implementation of a Waste Bank, which not only reduces waste generation but also increases environmental awareness through the 3R practice. Good knowledge of waste management is believed to encourage more positive behavior, so this study aims to analyze the relationship between increased knowledge and waste management behavior among students majoring in Environmental Health at the Padang Ministry of Health Polytechnic. The study used a cross-sectional design with 140 students as samples through total sampling. Data were obtained using a questionnaire that was measured. knowledge before and after the educational intervention as well as waste management behavior. The analysis was performed univariately and bivariately using the Chi-Square test. The results showed that of the 78 students who experienced an increase in knowledge, 57 (73.1%) had good waste management behavior. Meanwhile, in the group of students whose knowledge level remained the same (62 students), only 35 people (56.5%) exhibited good behavior. This finding indicates that students who experienced an increase in knowledge tended to have better waste management behavior than those who did not experience any change in knowledge. The Chi-Square test showed a p-value of 0.040, which means there is a significant relationship between increased knowledge and waste management behavior. In conclusion, increased knowledge contributes positively to students' waste management behavior. It is recommended that educational institutions strengthen education and the practice of waste banks on an ongoing basis, as well as develop collaborative programs to raise environmental awareness.